Intra-aortic balloon pump experience: a single center study comparing with and without sheath insertion - Özen, Yücel (J Cardiovasc Thorac Res, 2018)
Introduction: The mechanical circulation support used in treatment of low cardiac output at most is the intra-aortic balloon pump (IABP). Its usage fields are the complications occurring due to ischemic heart disease, disrupted left ventricle function, and the low cardiac output syndrome occurring during coronary artery by-pass surgery. Methods: During 28 years from 1985 to 2013, IABP support has been implemented to 3135 patients in our cardiac surgery operating theater and intensive care unit. The mean age of the patients was 61.4 ± 13.2 years (16-82). 2506 patients (80%) were the ones whom the cardiac surgery has been implemented. IABP support has been provided for 629 (20%) patients for medical treatment. We utilized IABP most frequently in coronary artery patients (70%). The first choice for placing the balloon catheter is the femoral artery in 3093 cases (98.7%). Results: The most frequently observed balloon complication was the lower extremity ischemia in 383 cases (12.2%).The leg ischemia was statistically significantly more frequent in patients with sheath (P=0.004). The extremity ischemia has developed in 4 of 12 patients with balloon placed from upper extremity. The local bleeding and balloon rupture were more frequent in patients whom the balloon has been placed without sheath. The mortality due to IABP has occurred in only 5 patients. Conclusion: Despite increase in IABP usage frequency rapidly, the complications due to catheter are still seen. We believe that the leg ischemia that is the most frequently seen complication can be prevented via IABP use without sheath.